PHENOMENA OF ECONOMIC CONTRACTION IN PANDEMI TIME: Inflation, Reference Interest Rate, Rupiah Exchange Rate & Money - Vanesa, Priskila (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
A pandemic is a health phenomenon that has hit the whole world, which has had a major impact on the fabric of life, including the economy. It was recorded that in 2020, Indonesia experienced an economic contraction due to a prolonged pandemic, causing uncontrolled economic activity, for example increasing inflation, falling exchange rates, and unstable money circulation. Based on this, this research was conducted to examine various factors that caused economic instability during the pandemic. In this research in the field of economics, quantitative fundamentals form the basis of the research, and in testing it uses statistical analysis of linear regression (cause and effect). Secondary research data obtained purposively from the national statistics center. The research data in question is inflation data, reference interest rates, the rupiah exchange rate and money supply during the pandemic. The results showed that the phenomenon of economic contraction occurred during the pandemic due to abnormal money circulation in society, because at that time many people refrained from consuming and other economic activities. Coupled with the increased value of interest rates, thus making people more careful in spending money.